THE RELATIONSHIP BETWEEN NUMERICAL ABILITY AND PEERS WITH STUDENT'S MATHEMATICS LEARNING OUTCOMES - Iqdam Iqdam; Widayati Widayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
This research is motivated by students' low numerical ability as a personal factor of students. Numerical ability and peers are suspected to be associated with poor student learning outcomes. This study aims to determine the presence or absence of a significant positive correlation between numerical skills and peers with learning outcomes in the eighth-grade student of Junior High School (SMP) Muhammadiyah Bligo Pekalongan in the academic year of 2017/2018. This study was classified as a quantitative study. This study's population was all eighth-grade students of SMP Muhammadiyah Bligo Pekalongan in 2017/2018, consisting of two classes with 42 students. Samples were taken by random sampling technique to the class and obtained the class VIIIA as a sample class with 21 students. Collection data techniques used questionnaires and test techniques. The testing instrument used validity and reliability. The prerequisite analysis test used the normality test, linearity, and independent test. Data analysis test for hypothesis testing using regression analysis and correlation analysis. The results showed that there is a positive and significant relationship between numerical ability and peers with math learning outcomes with Fcount = 12.50668 > Ftable = 3,59, with a correlation coefficient (R)Â  of 0.7716, and Å¶ = 6.84589 + 0.52719 X1 + 0.23563 X2 and Relative contribution X1 of 86.34459%, relative contribution X2 of 13.65541% and effective contribution X1 of 51.40671% and effective contribution X2 of 8.12997%.